The Power of a Controversial Issue; The Developmental Power of ‘Disruptive Moments’ for Both—Teachers and Students - Avest, Ina ter (Religions, 2020)
In Islamic primary education the subject of Islamic Religious Education (IRE) has a prominent place in the curriculum. In knowledge transfer and in behaving as a ‘good muslim’, aspects can be in conflict with generally accepted knowledge or customs in the Netherlands. The focus is on the power of a controversial issue (either or not wearing a head scarf) as a ‘disruptive moment’, stimulating pupils’ religious identity development. An example of recently developed teaching material illustrates the actual didactical approach regarding such a controversial issue. For a contextual understanding we start with a sketch of the Dutch educational system, and the position of Islamic education and its Islamic Religious Education (IRE) therein. In the second paragraph we describe the dialogical self theory (DST). DST’s relational understanding of a child’s development, including the developments regarding keeping a secret. In the third paragraph the case study is described, followed in the fourth paragraph by the introduction of Islamic teaching material and its way of approaching the controversial issue of the case study. We conclude our contribution with a discussion and recommendations for the development of teachers’ competencies in responding to controversial issues.